Predstavitev omrežja UMTS in njegova simulacija s pomočjo simulacijskega orodja Opnet Modeler - Mohorko, Jože (Informacije MIDEM, 2008)
Now days the use of mobile communications, applications and mobile data transfer are rapidly increased. The standardization work of GSM-based systems has begun in the 1980s, when the developing of unique radio communications system for Europe, at 900MHz, has started. Since then many modifications have been made in order to fulfill the increasing demand from the operators and cellular users. This paper describes a Universal Mobile Telecommunications Service (UMTS) network and an example of data reception, when web application and voice over internet protocol (VoIP) are used. The UMTS represent third generation (3G), broadband packet based transmission of text, video, digitized voice and multimedia at data rates up to 2 megabits per second (Mbps). The UMTS is intention for consistent set of services to mobile computers and phone users, no matter where they are located in the world. Third generation technology is based on the Global System for Mobile (GSM) communication standard. It is also endorsed by major standards, bodies and manufacturers, as the planned standard for mobile users around the world. Because UMTS is today fully available, computers and phone users can be constantly attached to the internet wherever they are, wherever they travel and as they roam, will have exactly the same set of capabilities. Users will have access through a combination wireless and satellite transmissions. Even today, some places are not fully covered with UMTS, so in that case, users can use multimode devices that switch to the currently available technology, such as GSM 900 and 1800 where UMTS is not yet available. UMTS offers many different applications like: light and heavy web browsing, reading web mail, VoIP quality speech, video conferencing, base access, telnet session, file transfer, file copy, GSM and PCM quality speech, SMS, MMS and so on. We pick out only two applications, and that is light web browsing and VoIP, which are today very popular for most population on the world, because many applications allow user to connect with the whole world at any place and any time. Under the third generation partnership project (3GPP) the third generation of UMTS cellular system was developed. The main parts of this systems are UMTS terrestrial radio access network (UTRAN), based on wide division multiple access (WCDMA) radio technology and GSM/EDGE radio access network (GERAN) based on global system for mobile telecommunications (GSM/enhanced data rates for global evolution (EDGE) radio technology). On the other hand the UMTS can be divided into three major parts: User Equipment (UE) that interfaces with the user and radio interface, UTRAN that handles all radio-related functionality, and the Core Network (CN), which is responsible for switching and routing calls and data connections to external networks. These elements are shown in Fig. 1. In second section the base UMTS elements and their function are presented on Fig. 2 and Fig. 3. Section 3 shortly represents the capabilities of the Opnet Modeler program and describes types of networks, which can be simulated. Section 4 represents the construction of UMTS network in the Opnet Modeler and describes the web application and VoIP. The web browsing is simulated in UMTS network application and object response time and page response time were observed. We located UMTS mobile node with name ,Web2- near UMTS transmitter. If we compare positions for both nodes (Fig. 4), is very simple to say, that is node,,Web2- closer to transmitter than node,,Webl,,. Both nodes are placed on fix position and both have identical parameters and identical settings, because of that, we can simply estimate remote distance influence at interdependence with object response time and page response time. Results of the simulations are shown on Fig. 5-6 and 8-9. Fig. 7 shows us UMTS structure for VoIP application. Section 5 concludes the paper.
Keywords: IP telefonija; komunikacijska omrežja; simulacije; spletne aplikacije; UMTS